128k views
14 votes
7x-4+8x=6x+8 abcdefghijklmnop

User Mghicks
by
5.3k points

2 Answers

9 votes

Answer:

x=
(4)/(3)

Explanation:

So the equation is 7x-4+8x=6x+8. All we need to do is simplify. On the left side, 7x+8x=15x, so 15x-4=6x+8. Now, we bring the 6x from the right side to the left. When you bring a term from one side to another, you change its sign. As of now, the sign of 6x is positive, so we make it negative and move it to the left side. The new equation is 15x-6x-4=8. Simplifying the left side gives you a new equation of 9x-4=8. Now we move the -4 from the left side to the right side. We change the sign so it becomes 4 and we move it to the right. The equation is now 9x=8+4. 8+4=12, so the final equation is 9x=12. Now we divide by 9 on both sides, giving us the unsimplified answer of x=
(12)/(9). We divide the numerator and the denominator by 3 and we get our final answer of x=
(4)/(3).

User Thivya
by
5.2k points
9 votes

Answer:

x = 4/3

Explanation:

7x − 4 + 8x = 6x + 8

User Balu K
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.